Modification of black-body radiance at low temperatures and frequencies - Falquez, Carlos; Hofmann, Ralf; Baumbach, Tilo (Annalen der Physik, 2010)
In contrast to earlier reports, where the spectrum of the energy density of photonic black-body radiation modified by SU(2) effects was discussed, we discuss the low-frequency spectrum of the radiance at temperatures ranging between 5 and 20 Kelvin. We conclude that compared to the conventional theory the only observable effect is associated with the spectral gap (total screening) which for T≥ 4.3 K scales with temperature T as ν*(T)
Gesehen am 13.02.2023